Modeling and Optimization of a Refrigeration System for Metro Train Air-conditioning - Yang Liang; Gao Jie; Zhang Chunlu (Zhileng xuebao)
Though metro in China today is booming, the typical refrigeration system for metro train air-conditioning is at quite lower energy efficiency level (COP = 2.2-2.3) in comparison with the residential systems under the same operating conditions. A refrigeration system model was developed to predict the metro train air-conditioning system performance. The predictions agreed well with the experimental data. Based on comprehensive modeling and analysis, the refrigerant circuitries of condenser and evaporator were optimized and smaller capacity compressor of higher COP was adopted. Consequently, the optimized system COP increased 21.7% at almost the same cooling capacity and cost. At last, the refrigerant R407C was replaced by R410A and the system were accordingly redesigned, which brought additional 11.3% COP increase and achieved 3. The present method and results could be valuable for designing high performance air-conditioning system of the metro train.